(untitled) (Research, Society and Development, 2024)
Introduction: Artificial Intelligence (AI) is transforming medicine, being able to perform diagnoses and propose therapeutic approaches. One example is Chat GPT, which has been gaining prominence. This study aims to explore the innovation of AI in medicine, highlighting its capabilities and challenges, especially in diagnoses, treatments and patient screening. Methodology: To validate the use of Chat GPT, a qualitative comparative thematic analysis was performed. Three scientific articles on insulin hypersensitivity reactions in patients with Diabetes Mellitus were selected. The cases were submitted to the tool, which suggested therapeutic approaches. These suggestions were then compared with the actual resolutions of physicians in clinical cases. Results: Chat GPT’s approaches coincided with those of physicians in several areas, such as insulin desensitization, personalized therapeutic regimen, insulin dosage adjustment, patient education and support, properly operating the DM diagnosis, glycemic control, focus on nursing care, monitoring and follow-up. However, there were divergences regarding the post-desensitization assessment, insulin therapy regimen, and treatment of dermatological complications. Thus, AI has shown to be impactful in the context of medical practice. Conclusion: In complex cases, such as insulin hypersensitivity, AI has shown consistent approaches, even with few precedents in the literature. Thus, the tool stands out as a promising innovation, with the potential to assist in medical practice, due to its reliability and practicality.